PROSES LITERASI HUKUM ADAT KAMPUNG TARUNG NUSA TENGGARA TIMUR : UPAYA PENGAKUAN EKSISTENSI - Miranda Risang Ayu Palar; Lailani Sungkar (Masalah-Masalah Hukum, 2019)
Legal means to obtain the recognition of indigenous communities in Indonesia are still scattered in a number of different regulations. Law on Village 2014 also obligates the government to arrange the system to conduct legal acknowledgements for Adat Villages. Tarung Village is a traditional village which situated in West Sumba Regency. The Members are still living in their own customary laws and embracing their local spiritual belief system as a living culture. Until recently, their village haven’t yet enjoyed the formal ackonwledgement they deserve as a united indigenous community nor as Adat Village. A number of mechanisms to obtain the acknowledgment require particular processes of identification and validation. This research is an initial effort to undertake the processes. In addition, it also aims to conduct a defensive legal protection by documenting the customary laws with interview method. The result displays the legal means to gain the existential acknowledgement which had been undertaken by the custodians of The Village and the Local Government.